2015
DOI: 10.1016/j.biortech.2015.01.136
|View full text |Cite
|
Sign up to set email alerts
|

Biorefining strategy for maximal monosaccharide recovery from three different feedstocks: Eucalyptus residues, wheat straw and olive tree pruning

Abstract: h i g h l i g h t sER, WS and OP are suitable feedstocks for Southern European biorefineries. The proposed biorefining strategy is efficient for monosaccharide recovery. Maximal monosaccharide recovery was obtained after autohydrolysis at 210°C. Maximal cellulose enzymatic digestibility was obtained after autohydrolysis at 230°C. The conditions for maximal sugar recovery yield were similar for all feedstocks. This work proposes the biorefining of eucalyptus residues (ER), wheat straw (WS) and olive tree prunin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
1
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 34 publications
4
23
1
4
Order By: Relevance
“…it is significantly higher than the glucose yieldreported for eucalyptus residues (54%), and close to 82% for olive tree pruning, and only slightly lower for straws (88, 90 and 91 %, respectively for rice, corn straw and wheat straw) [37][38][39], what may be explained by the higher lignin content of the cherimola seed cake as compared to straws.Although, it is reported that the highest glucose yield can only be achieved after the complete removal of hemicellulose, the lignin also plays a role on preventing cellulose hydrolysis that must not be neglected [22].…”
Section: Enzymatic Digestibility Of the Solid Residuesmentioning
confidence: 79%
“…it is significantly higher than the glucose yieldreported for eucalyptus residues (54%), and close to 82% for olive tree pruning, and only slightly lower for straws (88, 90 and 91 %, respectively for rice, corn straw and wheat straw) [37][38][39], what may be explained by the higher lignin content of the cherimola seed cake as compared to straws.Although, it is reported that the highest glucose yield can only be achieved after the complete removal of hemicellulose, the lignin also plays a role on preventing cellulose hydrolysis that must not be neglected [22].…”
Section: Enzymatic Digestibility Of the Solid Residuesmentioning
confidence: 79%
“…Paulownia tomentosa 41.7 ± 0.5 19.8 ± 0.3 61.5 20.5 ± 0.8 Paulownia fortune (Caparros et al, 2008) 34.2 22.7 56.9 27.2 Eucalyptus grandis (Castoldi and Bracht, 2014) 42 ± 4 19 ± 2 61.6 23 ± 2 Eucalyptus globulus (Ishiguro and Endo, 2015) 34.0 18.2 52.2 33.3 Eucalyptus residues (Silva-Fernandes et al, 2015) 36.1 ± 0.6 23.8 ± 0.8 59.9 26.7 ± 0.3 Bamboo timber (Xin et al, 2015) 39.36 ± 0.76 18.01 ± 0.06 57.37 20.83 ± 0.13 Bamboo knot (Xin et al, 2015) 39.90 ± 0.51 18.42 ± 0.55 58.32 21.90 ± 0.70 Water hyacinth (Poddar et al, 1991) 25.61 18.42 44.03 9.93 Water hyacinth (Chanakya et al, 1996) 33.97 18 51.97 26.36 Olive tree pruning (Silva-Fernandes et al, 2015) 24.5 ± 0.2 18.8 43.3 22.2 ± 0.2 Wheat straw (Toquero and Bolado, 2014) 35.19 ± 0.29 22.15 ± 0.21 57.34 22.09 ± 0.31 Corn stover 32.92 ± 0.51 16.53 ± 0.24% 49.45 17.36 ± 0.28 USA) after a two-section acid hydrolysis. Total reducing sugars in prehydrozate and hydrozate were determined by the DNS Method using glucose as the standard (Miller, 1959).…”
Section: Substratementioning
confidence: 98%
“…The samples collected were weighed and dried in an oven at 105 C until constant mass (Fallahi and Raoufat, 2008;Wood et al, 2014;Silva-Fernandes et al, 2015). And after that their moisture contents were calculated.…”
Section: Plant Residues and Their Characteristicsmentioning
confidence: 99%